2020
DOI: 10.1038/s41535-020-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic manifestation of domain-wall magnetism and magnetoelectric effect in a Néel-type skyrmion host

Abstract: We report a magnetic state in GaV 4 Se 8 which emerges exclusively in samples with mesoscale polar domains and not in polar monodomain crystals. It is manifested by a sharp anomaly in the magnetic susceptibility and the magnetic torque, distinct from other anomalies observed also in polar mono-domain samples upon transitions between the cycloidal, the Néel-type skyrmion lattice and the ferromagnetic states. We ascribe this additional transition to the transformation of distinct magnetic textures, confined to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(112 citation statements)
references
References 56 publications
6
105
0
1
Order By: Relevance
“…We identify characteristic positive-entropy precursor effects in the cycloid phase near the cycloid-to-skyrmion transition, which can be used to identify the phase boundary between these two states. Furthermore, we identify an unusual high entropy region at the low temperature, high-field phase boundary of the cycloidal state in GaV 4 Se 8 , which may be a signature of recently proposed magnetic phases confined to polar domain walls [32]. More generally, our results demonstrate that magnetoentropic mapping informed by computational models of entropic susceptibility can provide a rapid, unambiguous measurement of cycloid/skyrmion phase boundaries in model uniaxial systems and thereby facilitate the rapid characterization of similar skyrmion phase diagrams.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…We identify characteristic positive-entropy precursor effects in the cycloid phase near the cycloid-to-skyrmion transition, which can be used to identify the phase boundary between these two states. Furthermore, we identify an unusual high entropy region at the low temperature, high-field phase boundary of the cycloidal state in GaV 4 Se 8 , which may be a signature of recently proposed magnetic phases confined to polar domain walls [32]. More generally, our results demonstrate that magnetoentropic mapping informed by computational models of entropic susceptibility can provide a rapid, unambiguous measurement of cycloid/skyrmion phase boundaries in model uniaxial systems and thereby facilitate the rapid characterization of similar skyrmion phase diagrams.…”
Section: Introductionsupporting
confidence: 57%
“…This region does coincide with previously undetermined regions of the GaV 4 Se 8 phase diagram [10], which were proposed to arise due to distortions of cycloidal structure within limited structural domains. A more recent analysis of GaV 4 Se 8 has suggested that new, distinct magnetic phases may form at these fields and temperatures, confined to structural domain walls from the F43m → R3m structural transition [32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By increasing H, the stripe domains first fractured into small pieces and then transformed into skyrmions, owing to a delicate interplay of the interfacial DMI, magnetic anisotropy, dipolar interaction, and Zeeman interaction. [29][30][31] The critical magnetic field (H cri ), in which the stripe domains began to transform into skyrmions, was determined to be about 700 Oe for the current sample. When a compressive strain ε of −2.7% was applied, we observed a striking change in the field-dependent domain evolution during which the stripe domains directly transformed into out-of-plane ferromagnetic domains without the formation of any skyrmions (see the first row of Figure 2b).…”
Section: Strain Effects On Skyrmion Nucleationmentioning
confidence: 99%